Malaria research in India during 2003-2012: a bibliometric analysis. Issue 2 (1st April 2014) - K. Maharana, Rabindra
Abstract : Purpose: – The aim of this paper is to analyze Indian researchers' publications on malaria research and to serve as a guide to libraries needing to collect information on malaria. It also seeks to compare malaria affected Asian countries global rank with their publication and death rates. Design/methodology/approach: – For the purpose of the study Indian researchers' publication data which were indexed in Thomson Reuters Web of Science (WoS) were used. Various statistical techniques and bibliometric measures have been employed for further analysis. Findings: – The present study found out 2, 020 documents with h-index of 48, published by Indian researchers which were indexed in WoS during 2003 to 2012 and the majority of them were articles (81.43 percent). Malaria Journal is the most favored research journal among the Indian research community which covers 97 papers. A.P. Dash contributed maximum number of 136 (6.74 percent) papers. Council for Scientific and Industrial Research (CSIR) is the largest Indian funding agency with 184 (9.11 percent) research grants. Research limitations/implications: – Limitation by geographical area and time, i.e. the study only focuses the research publication of Indian researchers on malaria research during 2003 to 2012. Originality/value: – This is the first attempt to apply bibliometric techniques to analyze malaria research by Indian researchers, and, more generally for a country which is very badly affected by the disease.